THE CORRELATION BETWEEN SERUM SODIUM LEVELS AND THE SEVERITY OF CIRRHOSIS OF LIVER AND ITS COMPLICATIONS - PRADHAN, RUPA; TRIPATHY, DIPTIMAYEE; JALI, SIBANARAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The study aimed to assess the incidence of hyponatremia in cirrhosis of the liver and to evaluate the association between serum sodium levels and the severity of cirrhosis and its complications. Methods: Data on inpatients with cirrhosis of the liver were collected on the date of admission. The serum sodium levels on day 1 and the presence of complications and their severity in 100 patients were analyzed. Results: The incidence of dilutional hyponatremia, which was subdivided into three groups (mmol/L): A-≤130, B-131-135, and C-≥136, were 55%, 25%, and 20%, respectively. The severity of liver cirrhosis was assessed using the CTP score and the MELD score, with a higher score seen in Group A (p=0.011 and p=0.012), respectively. Furthermore in group A, higher grades of complications were seen: grade 3/gross ascites (p=0.001), grade lll/lV hepatic encephalopathy (p=0.007), spontaneous bacterial peritonitis (p=0.049), and hepatorenal syndrome (p=0.022). Even in group B with s.Na+level 131–135 mmol/L, the development of complications was no less common. Conclusion: Serum sodium levels must be closely monitored in cirrhotic patients as they suggest the possibility of a potentially negative impact on the clinical course of the disease.